Functional Nanocellulose Derivatives for Global Environmental Solutions - Perdana, Rini (CV. Science Tech Group, 2024)
Nanocellulose, a sustainable and biodegradable material derived from natural cellulose, holds immense potential for addressing global environmental challenges. This article reviews the production methods, structural modifications, and applications of nanocellulose derivatives in environmental contexts, emphasizing their role in water purification, pollutant adsorption, and renewable energy solutions. The systematic literature review highlights the unique properties of nanocellulose, such as high mechanical strength, large specific surface area, and tunable chemical functionalities, which enable its use in various industrial, biomedical, and environmental applications. Results indicate that nanocellulose-based materials outperform conventional materials in efficiency and sustainability, particularly in water treatment and biodegradable packaging. Despite its advantages, challenges remain, including production costs, dispersibility in polymer matrices, and stability under high humidity. These limitations necessitate further research and collaborative innovation to enhance its applicability and affordability.